2012
DOI: 10.1002/clen.201200198
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Power by Microbial Fuel Cell with Ferricyanide in Biodegradation of Benzene

Abstract: The power generation potential of a microbial fuel cell (MFC) during the process of benzene biodegradation with potassium ferricyanide (0–200 mM) as the terminal electron acceptor was evaluated. Experimental results demonstrate that benzene was used as the sole carbon source in generating electricity by a mixed culture. The power density increased from 0.0276 to 2.1 mW m−2 as the concentration of potassium ferricyanide in the cathode chamber was increased from 0 to 200 mM. With a benzene concentration of 10.87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…However, they are comparable with values obtained in the MFC systems treating waters contaminated with petroleum hydrocarbons, e.g. benzene (Wang et al, 2012;Rakoczy et al, 2013;Wu et al, 2013), where power densities from 0.85 to 2.1 mW m -2 were reported. Recently, a maximum power density of 316 mW m -3 NAC (net anodic compartment) and a coulombic efficiency of 14% was obtained in a lab-scale MFC treating the same groundwater contaminated with benzene, MTBE and NH 4 + -N as used in the present study, in which graphite granules were used as electrode materials (Wei et al, 2015).…”
Section: Polarization and Power Density Curvessupporting
confidence: 88%
See 1 more Smart Citation
“…However, they are comparable with values obtained in the MFC systems treating waters contaminated with petroleum hydrocarbons, e.g. benzene (Wang et al, 2012;Rakoczy et al, 2013;Wu et al, 2013), where power densities from 0.85 to 2.1 mW m -2 were reported. Recently, a maximum power density of 316 mW m -3 NAC (net anodic compartment) and a coulombic efficiency of 14% was obtained in a lab-scale MFC treating the same groundwater contaminated with benzene, MTBE and NH 4 + -N as used in the present study, in which graphite granules were used as electrode materials (Wei et al, 2015).…”
Section: Polarization and Power Density Curvessupporting
confidence: 88%
“…Recently, it was reported that microbial anodes in METs can effectively enhance the anaerobic biodegradation of petroleum hydrocarbons (e.g. benzene, toluene), providing potential applications for the bioremediation of anaerobic sediment or groundwater contaminated with petroleum hydrocarbons (Zhang et al, 2010;Wang et al, 2012;Wu et al, 2013). In addition to converting the chemical energy of pollutants in electricity, METs were used as biosensors for on-line monitoring of wastewater treatment or anaerobic digestion processes, such as MFC-based sensors for measuring the biological oxygen demand (BOD) (Di Lorenzo et al, 2009;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In MFCs, the anode electrode acted as the terminal electron acceptor but failed to induce a repression similar to sulfate or nitrate for the methanogenic pathway (Wu et al, ). A previous study showed that the maximum output voltage obtained from benzene degradation in a double‐chamber MFC was 96 mV, and the average benzene removal rate was around 100% (Wu et al, ). The maximum voltage value is consistent with results obtained in this study except for the benzene removal.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum voltage value is consistent with results obtained in this study except for the benzene removal. It is worth noting that the initial concentration of benzene used in Wu’s study was around 20 mg/L, and potassium ferricyanide was used as terminal electron acceptor (Wu et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation